PERSPECTIVES OF THE USAGE OF HYDROPOWER POTENTIAL OF THE RIVERS OF THE DNIPRO RIVER BASIN (ON THE EXAMPLE OF THE ROS RIVER) - Obodovskiy, O.; Onischuk, V.; Pochaievets, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
A new scientific and technological approach concerning the high level of ecological usage of hydropower potential of rivers in the Dnipro river basin is presented. The constructive and layout solutions for the declared small high-ecological hydroelectric power plants are presented. Examples of hydraulic calculation of pressure derivation are given and the power of a hydroelectric power plant is determined taking into account the effect of an additional electromagnetic field on its individual working bodies. The Ros is taken as the pilot river, which shows the locations of universal small high-ecological hydroelectric power stations and their main operating characteristics. In addition, recommendations are made regarding the rational allocation of hydroelectric power plants, taking into account the type of channel. The scientific novelty of the new technological approach is the use of an additional local electromagnetic field at the end of the pressure pipeline at a section length of at least 10 m, on the nozzle and on the turbine. The presence of an electromagnetic field around the turbine and generator enables the stations to operate at significant speeds (from 600 to 16 thousand revolutions per minute). In addition, in the background of the electromagnetic field, due to the absence of friction in the bearings, the life of turbines and generators increases. The universality of new hydroelectric power plants is explained by the fact that such stations can be used on any water facility (mountain or plain river, lake, reservoir or near the reservoir). The technical and economic efficiency of high-ecological hydroelectric power plants is assessed by the high level of environmental safety of the water object, the cost-effectiveness of construction and the achieved level of safety during flood passage, which is achieved by minimal interference and water use of the water object. In addition, the work of the station is effective at the minimum volume of water drain on any part of the river, almost without violating the hydroecological parameters of the water object. Comparative analysis of the estimated cost of a small hydroelectric power station near the village is presented.
Keywords: river; high-ecological small hydroelectric power station; hydromorphological state of the river; technological paradigm of the use of working parts of derivation; electromagnetic field